Are dancers symmetrical during single leg and double legged landings? - Conway, C. K.; Bradshaw, E. J.; Salo, A. I. T. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The effect of limb preference on lower extremity function and performance was examined in young healthy dancers. Fifteen elite adolescent dancers performed 15 consecutive single leg hops on each leg and 3 rebound jumps onto two triaxial force platforms. To identify limb preference the Waterloo Footedness Questionnaire was administered. Functional symmetry indices (SI) were calculated for the peak landing forces, and limb dominance was identified as the limb producing the greatest take-off power during the rebound jumps. Significant asymmetry was identified in the landing performance of the dancers. However no relationship was found between limb preference and limb dominance of the dancers. In conclusion, dance teachers should aim to achieve safer landing strategies by developing ambidextrous movement in young dancers.